Nanoparticles Derived from Active Metabolites of Chaetomium cupreum CC3003 against Phytophthora Rot of Durian - Rujira Tongon; Kasem Soytong (International Journal of Agriculture and Biology, 2021)
Phytophthora rot of durian (Durio zibetinus L.) is a serious disease wherever the crop has been planted and the disease control customarily uses chemical fungicides reported to be resistant by pathogen. Alternative non-chemical control strategies are being investigated to produce safe food. The main objective of this research was to test the activity of metabolites from Chaetomium cupreum CC3003 in the form of crude materials and nanoparticles to control and induce immunity to Phytophthora palmivora causing rot of durian var. Monthong. The results showed that P. palmivora proved to be pathogenic to durian var. Monthong. C. cupreum CC3003 acted as an antagonist and P. palmivora was confirmed as the pathogen by morphological and molecular genetic identification. Effective doses (ED50) of CC-E, CC-H and CC-M crude metabolites for spore inhibition were 60, 97 and 140 mg.kg - , respectively. The research findings found that the diameters of nano CC-E, nano CC-H and nano CC-M were 534, 499 and 537 nm, respectively. The nano CC-E, nano CC-H and nano CC-M demonstrated antifungal activity against P. palmivora with ED50 of 11, 13 and 16 mg.kg - , respectively. The nanoparticles at low concentrations were more effective than crude metabolites at high concentrations. Nano-CC-E used to treat seedlings of durian resulted in the production of scopoletin which served as an immunity agent or elicitor against rot disease of durian. It is concluded that active metabolites derived from C. cupreum significantly inhibited P. palmivora and induced immunity through phytoalexin production.
Keywords: Medicinal Plant Research; Natural Products and Applications; Coconut Research and Applications